Lingkar Pinggang Berkorelasi dengan Kadar Gula Darah Sewaktu Pada Lansia dengan DM: Waist Circumference Correlates with Random Blood Sugar Levels in Elderly with DM - Tanty Anggi Wulandari; Suwanti (Journal of Holistics and Health Sciences, 2024)
Indonesia is one of the top 10 countries with the highest number of DM sufferers. It is predicted to rise to fifth place in 2025 ( number of sufferers of 12.4 million people). One of the factors that influences the occurrence of DM is nutritional status, both obesity and central obesity. Central obesity can be seen from measuring the waist circumference ratio. Achieving good nutritional status is always associated with blood glucose levels. This study aims to determine and analyze the relationship between waist circumference and blood sugar levels in the elderly. The research design used is quantitative research with a cross-sectional survey approach. The population is all elderly people suffering from DM at the Pandu Senjaya Community Health Center in March-April 2024, totaling 58 people. The sample was 58 respondents with a total enumerative sampling technique. The results were 27 elderly people had a waist circumference in the normal category and 31 elderly people had an abnormal waist circumference. Most of the elderly had poor GDS, 38 elderly (65.5%). There is a relationship between waist circumference and blood sugar levels in the elderly at the Pandu Senjaya Community Health Center(p value 0.033)(α=0.05)). It is recommended that the elderly maintain their diet, increase physical activity and manage stress  to avoid obesity which results in DM.   ABSTRAK Indonesia merupakan salah satu dari 10 besar negara dengan jumlah penderita DM terbanyak. Diprediksikan akan menjadi peringkat ke-5 pada tahun 2025 (jumlah penderita 12,4 juta jiwa). Salah satu faktor yang mempengaruhi terjadinya DM adalah status gizi baik obesitas maupun obesitas sentral. Obesitas sentral dapat dilihat dari pengukuran rasio lingkar pinggang. Pencapaian status gizi yang baik berkaitan dengan kadar glukosa darah. Penelitian ini bertujuan mengetahui dan menganalisis hubungan antara lingkar pinggang dengan kadar gula darah sewaktu pada lansia. Desain penelitian yang digunakan yaitu penelitian kuantitatif dengan pendekatan cross-sectional. Populasi yaitu seluruh lansia penderita DM di Puskesmas Pandu Senjaya bulan Maret-april 2024 sejumlah 58 orang. Sampel sebanyak 58 responden dengan teknik total enumerative sampling. Hasil dari penelitian yaitu lansia dengan lingkar pinggang kategori normal sejumlah 27 lansia dan tidak normal 31 lansia. Sebagian besar lansia  memiliki GDS (Gula Darah Sewaktu) buruk sebanyak 38 lansia (65.5%). Terdapat hubungan antara lingkar pinggang dengan kadar gula darah sewaktu pada lansia di Puskesmas Pandu Senjaya (p value  0.033) (α=0.05). Disarankan kepada lansia agar menjaga pola makan, meningkatkan aktifitas fisik, dan mengelola stres sehingga terhindar dari obesitas yang berakibat terkena penyakit DM.